2017
DOI: 10.1073/pnas.1616659114
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cortical elasticity in Drosophila melanogaster embryos using ferrofluids

Abstract: Many models of morphogenesis are forced to assume specific mechanical properties of cells, because the actual mechanical properties of living tissues are largely unknown. Here, we measure the rheology of epithelial cells in the cellularizing Drosophila embryo by injecting magnetic particles and studying their response to external actuation. We establish that, on timescales relevant to epithelial morphogenesis, the cytoplasm is predominantly viscous, whereas the cellular cortex is elastic. The timescale of elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(185 citation statements)
references
References 27 publications
11
174
0
Order By: Relevance
“…This suggests that the initially solid-like tissue may be poised near this transition to allow for rapid cell rearrangement and tissue flow with small changes in cell properties or under small applied forces, while still maintaining tissue integrity. This is possibly consistent with recent ferrofluid droplet and magnetic bead microrheology measurements of tissues in the cellularizing Drosophila embryo prior to axis elongation, which indicated that tissue behavior is predominantly elastic (solid-like) over timescales less than several minutes (45,46). While both studies compared the long-time tissue behavior to fluid-like viscous models, their observations might also be consistent with a weak yield-stress solid, which is solid-like for small stresses but deforms plastically and flows for larger stresses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This suggests that the initially solid-like tissue may be poised near this transition to allow for rapid cell rearrangement and tissue flow with small changes in cell properties or under small applied forces, while still maintaining tissue integrity. This is possibly consistent with recent ferrofluid droplet and magnetic bead microrheology measurements of tissues in the cellularizing Drosophila embryo prior to axis elongation, which indicated that tissue behavior is predominantly elastic (solid-like) over timescales less than several minutes (45,46). While both studies compared the long-time tissue behavior to fluid-like viscous models, their observations might also be consistent with a weak yield-stress solid, which is solid-like for small stresses but deforms plastically and flows for larger stresses.…”
Section: Discussionsupporting
confidence: 86%
“…Cell stretching along the AP axis also contributes to tissue elongation and coincides with movements of neighboring tissues (26-28, 42, 43), indicating that external forces play an important role in tissue behavior. Despite significant study of this tissue, a comprehensive framework for understanding its mechanical behavior is lacking, in part because direct mechanical measurements inside the Drosophila embryo, and more generally for epithelial tissues in vivo, continue to be a challenge (44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…This generates a Brillouin spectrum where the scattered light displays a frequency shift compared to the illumination light, from which the longitudinal modulus can be measured if the refractive index and density of the material is known. MBs-based methodologies have been used to measure viscoelastic properties of embryonic tissues such as elasticity of the trophectoderm and inner cell mass of the mouse blastocyst and mouse limb bud (preprint: Zhu et al, 2018) and Young modulus, shear viscosity and bulk viscosity of the Drosophila blastoderm during cellularization (Doubrovinski et al, 2017;D'Angelo et al, 2019). In addition, from the linewidth of the Brillouin peaks the viscosity of the tissue can be obtained (preprint: Prevedel et al, 2019).…”
Section: Rheologymentioning
confidence: 99%
“…By monitoring the extend of the bead movement during the application and removal of the magnetic force, the viscoelastic properties of the surrounding tissue can be quantified using simple mechanical models (Savin et al, 2011). MBs-based methodologies have been used to measure viscoelastic properties of embryonic tissues such as elasticity of the trophectoderm and inner cell mass of the mouse blastocyst and mouse limb bud (preprint: Zhu et al, 2018) and Young modulus, shear viscosity and bulk viscosity of the Drosophila blastoderm during cellularization (Doubrovinski et al, 2017;D'Angelo et al, 2019). Similar to the FDs, measuring tissue rheology through MBs at larger scales requires insertion of multiple beads within the tissue and the application of a uniform and strong magnetic field, a non-trivial approach when, e.g., using magnetic tweezers.…”
Section: Rheologymentioning
confidence: 99%
“…Beside the force generating mechanism, the material properties of the embryos (22)(23)(24) may influence the movement of the nuclei. The actin cytoskeleton inhibits short time-scale movements (21) and promotes ordering of the nuclear array (14).…”
Section: Introductionmentioning
confidence: 99%